An evaluation of the mechanical properties of Type III and Type IV gypsum mixed with two disinfectant solutions - Roy Sunitha; Sridevi J; Kalavathy N (Wolters Kluwer Medknow Publications, 2010)
Background and Objectives: This in-vitro study was conducted to evaluate the strength and properties of Type III and Type IV gypsum mixed with disinfectant solutions. Materials and Methods: Type III and Type IV gypsum were used for the study. Three different mixing solutions namely waterqueous solutions of 0.525% sodium hypochlorite and 2% glutaraldehyde were used. Gypsum materials were subjected to further modification by adding a mixture of 1.0% gum arabic and 0.132% calcium hydroxide before mixing with the disinfectant solutions, at two different liquid/powder (L/P) ratios for each. Both, the unmodified and the modified gypsum were tested for compressive and tensile strength after one hour and one week from the start of the mix. The crystalline configuration of the fracture fragments of the unmodified and modified set gypsum were studied under the scanning electron microscope. Results: The disinfectant solutions reduced the strength of both Type III and Type IV gypsum. Water showed higher-strength, which was followed by 0.525% sodium hypochlorite and 2% glutaraldehyde. The modified Type III and Type IV gypsum with reduced L/P ratio also showed strength values less than that of the control groups. Interpretation and Conclusion: Chemical disinfectants reduced the strength of gypsum when used as water substitutes. Gum Arabic and calcium hydroxide additives permitted lower L/P ratio, however, there was still excess water retained in the set gypsum that lowered the strength values of Type III and Type IV gypsum. Hence, further reduction of L/P ratio may increase the properties of the modified Type III and Type IV gypsum.